Molecular Basis and Role of Siglec-7 Ligand Expression on Chronic Lymphocytic Leukemia B Cells - Chang, Lan-Yi; Liang, Suh-Yuen; Lu, Shao-Chia; Tseng, Huan Chuan; Tsai, Ho-Yang; Tang, Chin-Ju; Sugata, Marcelia; Chen, Yi-Ju; Chen, Yu-Ju; Wu, Shang-Ju; Lin, Kuo-I; Khoo, Kay-Hooi; et al. (Frontiers in Immunology, 2022)
Siglec-7 (sialic acid–binding immunoglobulin-like lectin 7) is an immune checkpoint-like glycan recognition protein on natural killer (NK) cells. Cancer cells often upregulate Siglec ligands to subvert immunosurveillance, but the molecular basis of Siglec ligands has been elusive. In this study, we investigated Siglec-7 ligands on chronic lymphocytic leukemia (CLL) B cells. CLL B cells express higher levels of Siglec-7 ligands compared with healthy donor B cells, and enzymatic removal of sialic acids or sialomucins makes them more sensitive to NK cell cytotoxicity. Gene knockout experiments have revealed that the sialyltransferase ST6GalNAc-IV is responsible for the biosynthesis of disialyl-T (Neu5Acα2–3Galβ1–3[Neu5Acα2–6]GalNAcα1–), which is the glycotope recognized by Siglec-7, and that CD162 and CD45 are the major carriers of this glycotope on CLL B cells. Analysis of public transcriptomic datasets indicated that the low expression of GCNT1 (encoding core 2 GlcNAc transferase, an enzyme that competes against ST6GalNAc-IV) and high expression of ST6GALNAC4 (encoding ST6GalNAc-IV) in CLL B cells, together enhancing the expression of the disialyl-T glycotope, are associated with poor patient prognosis. Taken together, our results determined the molecular basis of Siglec-7 ligand overexpression that protects CLL B cells from NK cell cytotoxicity and identified disialyl-T as a potential prognostic marker of CLL.